Semiochemical-mediated Management of Thrips: Current Advances and Future Prospects - Sadafale, Gaurav Vinod Rao; Shashikala, B.; Madarakhandi, Vinayak; Munj, Sujal Suhas; Benakashree, C.; Niharika, Gokavaram; Kondaguri, Sachin R. (International Journal of Bio-resource and Stress Management, 2026)
This review synthesized current knowledge on semiochemicals produced by thrips, host plants, and their synthetic analogs, emphasizing their ecological roles and applications in integrated pest management (IPM). Thrips (Thysanoptera) were among the most destructive pests of agricultural, horticultural, and ornamental crops worldwide. Their economic impact results from both direct feeding injury and their capacity to transmit tospoviruses, leading to substantial yield losses. Conventional management has relied mainly on chemical insecticides; however, issues such as insecticide resistance, pest resurgence, environmental contamination, and growing consumer demand for residue-free produce have highlighted the urgency for sustainable alternatives. Semiochemicals were behavior-modifying chemicals mediating inter- and intraspecific interactions offered promising opportunities in thrips management. Recent advances have identified aggregation pheromones, plant-derived kairomones, and allomones that could influence thrips behavior. These compounds have been effectively utilized in strategies such as mass trapping, monitoring, and push–pull systems that combine attractants and repellents to manipulate pest movement. Synthetic analogs of natural compounds have further enhanced the stability and field applicability of these tools. Despite their potential, several challenges remained before semiochemical-based management could be widely adopted. These included the need for large-scale field validation, development of cost-effective formulations, optimization of delivery systems, and integration with other pest management tactics within multi-pest frameworks. Future research should focus on understanding species-specific behavioral responses, improving semiochemical blends, and promoting their incorporation into holistic IPM programs. Harnessing these chemical cues could contribute to sustainable, eco-friendly, and economically viable approaches for thrips control.